Six hundred meter-run and broken 800`s contribution to pacing improvement in eight hundred meter-athletics: role of expertise and training implications - Blasco-Lafarga, C.; Montoya-Vieco, A.; Martinez-Navarro, I.; Mateo-March, M.; Gallach, J. E. (The Journal of Strength and Conditioning Research, 2013)
Little is known about the influence of speed endurance workouts on the improvement of pacing strategies in the 800-m running event. This study aims to analyze it, comparing continuous repetitions vs. interval training workouts. Because we hypothesize that pacing is susceptible to expertise, there might be age differences. Nineteen male 800-m runners (age: 21.36 ± 5.26, season best [SB]: 117.14 ± 5.18 seconds) were tested. Athletes were asked to run 1 × 600 m (6r) at 100% (SB) and 2 × 4 (200 m per 30 seconds) per 15 minutes (B8) at 102% (SB), counterbalanced and randomized within 1 week of difference. Pacing strategy (velocity dynamics) was analyzed by means of time differences in 200-m segments (T200), whereas age category was considered a grouping factor (younger than 23 years-senior, n = 10; vs. juvenile-junior, n = 9; 25.29 ± 4.32, 17.00 ± 0.66 years). Blood lactate was registered after 6r, B81, and B82 bouts. Univariate contrast analysis revealed a significant decrease in velocity during 6r (p < 0.001; 9.33% between first and third segment), thus a positive pacing, whatever the age category. B8 shared this final significant impairment (p < 0.001), although it was smaller (5.73% drop for B81; 8.47% for B82), and neither linear nor significant among consecutive T200. B8 also showed significant differences (p < 0.05) in the interaction sampling condition × age category. The T test added blood lactate significant differences (B82: 15.42 ± 1.16, B81: 12.25 ± 2.03 and 6r: 13.58 ± 1.82 mmol/L). Summarizing, both methods share a positive pacing, confirming to be related to enhancing energy systems and coping final fatigue in the 800 m. Continuous 6r preserves the nature and tempo of the 800 m, although 1 repetition is metabolically limited. Interval B8 allows larger amounts of high intensity running, enhancing neuromuscular benefits jointly with higher lactate productions. Significant age category differences in B8 indicate that pacing capacity may improve with expertise and interval workouts may be appropriate methods to manage it.